Kapitał pracujący a płynność finansowa i rentowność przedsiębiorstw rolniczych - Wasilewski, Mirosław (Working Capital in Relation to Liquidity and Agricultural Enterprises' Profitability, 2007)
The paper presents the analysis of relations between a working capital level in agricultural enterprises and their situation concerning liquidity, profitability and assets-capital relations. Enterprises of the highest value of working capital were characterized by the best liquidity, the highest relation of working assets to fixed assets and domination of equity. However, too conservative financing strategy in these enterprises caused decrease of return on assets and sale. Enterprises of the lowest working capital were threatened by loss of liquidity and usually made losses. Involvement of loan capital was higher in enterprises of more than average level of working capital than in enterprises of the highest working capital. Moreover, relation of working assets to fixed assets was more advantageous in the enterprises, what resulted in gaining usually the highest profitability ratios while liquidity was kept.The paper presents the analysis of relations between a working capital level in agricultural enterprises and their situation concerning liquidity, profitability and assets-capital relations. Enterprises of the highest value of working capital were characterized by the best liquidity, the highest relation of working assets to fixed assets and domination of equity. However, too conservative financing strategy in these enterprises caused decrease of return on assets and sale. Enterprises of the lowest working capital were threatened by loss of liquidity and usually made losses. Involvement of loan capital was higher in enterprises of more than average level of working capital than in enterprises of the highest working capital. Moreover, relation of working assets to fixed assets was more advantageous in the enterprises, what resulted in gaining usually the highest profitability ratios while liquidity was kept.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 617-627